Ekaristi: Akar Segala Kekudusan menurut R. Cantalamessa dan Benediktus XVI - Veronika Puji Astuty (P3TK, Sanata Dharma University, 2020)
The Church as the mystical body of Christ is called to sanctification (LG 42). The Churchs challenge to live up to the vocation of sanctification faces the challenge of antrophocentrism in modern times. The dissemination of antrophocentrism in modern times have shaped the emergence of new concepts, namely rationalism, individualism, and secularism, making humans to be apathetic and leading to a superficial spiritual life. The severity of the challenges experienced by the Church in modern times demands militancy of the spiritual life that is rooted in the Eucharist. This article aims to discuss the Eucharist as the root of all forms of the Church sanctification in the world as viewed by Raniero Cantalamessa and Pope Benedict XVI. Both Cantalmessa and Pope Benedict XVI show that the sanctification within the Church is rooted in the Eucharist. Through Eucharist as the real encounter, The Church is transformed by the divine power of Christ which revives, moves, supports, and strengthens the pilgrimage of Church in this world. The writer approaches this problem by scrutinizing the viewpoints by Raniero Cantalamessa and Pope Benedict XVI by carrying out the critical history method and library research. Then, the writer synthesizes the two viewpoints on the Eucharist as the root of sanctification. This writing is expected to be a viewpoint contribution to spiritual life of all Christians in living the call to the sanctification.